âKORUPSI SEJARAHâ DALAM ISLAM - Edi Susanto, Edi Susanto (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstractThis article tries to show that the internal conflicts amongÂ  the ummah have broken sinceÂ  theÂ Â  earlyÂ  periodÂ  of Islam. The critical study of early Islamic periodÂ  to uncover the historical distortions was regarded dangerousÂ  and painful .Â  A critical study ofÂ  this early period will give us a new description of this period based on a strong data; and this critical history leads us to realize that such critical study will not violate the sacredness of Islam..Kata-kata kuncikorupsi sejarah, al-Khulafaâ al-Rasyidun, Dinasti Umayah, Dinasti Abbasiyah